PENGEMBANGAN KOMIK DIGITAL INTERAKTIF PADA MATERI TRADISI MASYARAKAT SEKITAR “PETIK LAUT” UNTUK KELAS III SD - Fernanta W, Bernard Bagus; Made Padmarani Sudewiputri; Ni Putu Juni Artini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an interactive digital comic with the theme of the local community tradition "Petik Laut" for third-grade elementary school students. The background of this study is based on the importance of integrating local wisdom values ​​into the elementary school curriculum to build contextual understanding and patriotism from an early age. The method used in this study is research and development (R&D) with the ADDIE model. Feasibility data collection was carried out through a validation sheet by a team of experts (juries), while practicality data was obtained through a teacher response questionnaire. The results of the study indicate that the developed interactive digital comic meets the highest feasibility criteria. Based on the validation test, the aspects of content feasibility, presentation feasibility, and language feasibility each obtained a percentage of 100% with a very valid category. Meanwhile, the results of the practicality test by teachers also reached a percentage of 100% with a very practical category, which confirms that this media is easy to operate, has high visual appeal, and is functional in the classroom. The limitations of this study lie in the evaluation of practicality which is still centered on teachers and the lack of direct effectiveness testing on student learning outcomes in the field. The conclusion of this study is that the interactive digital comic "Petik Laut" is highly suitable and practical for use as a local culture learning medium for third-grade elementary school students. The implications of this research are expected to be innovative, alternative and engaging learning technologies, as well as a medium for preserving local culture in the digital age.